2000
DOI: 10.1111/j.1545-5300.2000.39306.x
|View full text |Cite
|
Sign up to set email alerts
|

Empathy in Families of Women with Borderline Personality Disorder, Anorexia Nervosa, and a Control Group*

Abstract: This is a study of empathy in the families of 27 women with borderline personality disorder (BPD), 28 women with restricting anorexia nervosa (AN), and 27 women without a clinical diagnosis (NC). The daughters and both parents responded to the Interpersonal Reactivity Index (IRI), an instrument for assessing four dimensions of empathy. In addition, they were personally interviewed, with the Family Interview for Protectiveness and Empathy (FIPE), about the extent of empathy expressed by the parents to their dau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
80
3
14

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 45 publications
5
80
3
14
Order By: Relevance
“…Several authors [25][26][27] have argued that responses to the pain of another can be considered on a maturational gradient determined by self -other control. Under these models, PD is considered to be an immature response to another's pain in which representation of the other's pain is unable to be inhibited, to the extent that the observer feels a significant degree of negative arousal.…”
Section: Impairments In Self -Other Control (A) Autism Spectrum Disordermentioning
confidence: 99%
“…Several authors [25][26][27] have argued that responses to the pain of another can be considered on a maturational gradient determined by self -other control. Under these models, PD is considered to be an immature response to another's pain in which representation of the other's pain is unable to be inhibited, to the extent that the observer feels a significant degree of negative arousal.…”
Section: Impairments In Self -Other Control (A) Autism Spectrum Disordermentioning
confidence: 99%
“…An instructive example is provided in the work of Guttman (2000) in a study of 16-to 40-year-old females. Independent variables for the analysis of variance were based on meeting the criteria in the Diagnostic and Statistical Manual of Mental Disorders (3rd ed., revised; American Psychiatric Association, 1987) for the clinical conditions of anorexia nervosa and borderline personality disorder.…”
Section: Anovamentioning
confidence: 99%
“…Findings from cross-sectional studies reported low empathy and conflicting family relationships (Allen et al, 2005;Gunderson & Lyoo, 1997), contradictory family communication patterns (Guttman & Laporte, 2000), and lack of perceived protection by mothers (Lyons-Ruth, Choi-Kain, Pechtel, Bertha, & Gunderson, 2011) in families of adults with BPD when compared to both normative and clinical controls.…”
mentioning
confidence: 99%